From Skeptic to Vital Partner in Massage Therapy Research: an Interview with Mark Hyman Rapaport, MD - Kennedy, LMT, BCTMB, DrPH, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2018)
Mark Hyman Rapaport, MD is a highly accomplished researcher, academician, and clinician. Dr. Rapaport has more than 180 publications, and his main research interests include biologic genesis of anxiety disorders, as well as immunity abnormalities and depression in mood disorders. His research investigating massage therapy has included study of inflammatory biomarkers, cancer related fatigue, and generalized anxiety disorder. He has created a successful partnership with the Atlanta School of Massage for the implementation of his research inquiry. Dr. Rapaport discusses with us a wide range of topics on massage therapy, including from where his inspiration for research comes.